2017
DOI: 10.7554/elife.23242
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L1 promotes skin tumorigenesis independently of β-catenin through induction of LCN2

Abstract: The transcription factor TCF7L1 is an embryonic stem cell signature gene that is upregulated in multiple aggressive cancer types, but its role in skin tumorigenesis has not yet been defined. Here we document TCF7L1 upregulation in skin squamous cell carcinoma (SCC) and demonstrate that TCF7L1 overexpression increases tumor incidence, tumor multiplicity, and malignant progression in the chemically induced mouse model of skin SCC. Additionally, we show that downregulation of TCF7L1 and its paralogue TCF7L2 reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 73 publications
(126 reference statements)
0
16
0
Order By: Relevance
“…2, B and C ; and Table S1 ). In contrast and notably, expression of typical growth-promoting and transforming Wnt coactivators such as Bcl9 ( Mani et al, 2009 ), the skin tumor promoter Tcf7L1 ( Ku et al, 2017 ), Wnt antagonists such as APC2, a component of the destruction complex targeting β-catenin, and DKK4 were down-regulated (up to 3.5-fold). In support of Wnt signaling promoting premature cell cycle exit of progenitor cells, pro-proliferative gene products implicated in cell cycle progression were down-regulated (up to 16-fold).…”
Section: Resultsmentioning
confidence: 93%
“…2, B and C ; and Table S1 ). In contrast and notably, expression of typical growth-promoting and transforming Wnt coactivators such as Bcl9 ( Mani et al, 2009 ), the skin tumor promoter Tcf7L1 ( Ku et al, 2017 ), Wnt antagonists such as APC2, a component of the destruction complex targeting β-catenin, and DKK4 were down-regulated (up to 3.5-fold). In support of Wnt signaling promoting premature cell cycle exit of progenitor cells, pro-proliferative gene products implicated in cell cycle progression were down-regulated (up to 16-fold).…”
Section: Resultsmentioning
confidence: 93%
“…In cancer, the role of TCF7L1 remains poorly understood, and appears to be cell-type specific. For example, TCF7L1 expression has been linked to promotion of cell proliferation and tumor growth and an increase of sphere formation in breast cancer 25 , colorectal cancer 26 and skin squamous cell carcinoma 28 . In contrast, it has been shown that ectopic expression of TCF7L1 inhibits self-renewal of liver cancer stem cells 24 , which are believed to play a prominent role in tumor relapse and metastasis 37 , thus highlighting a potential role of TCF7L1 in the stemness-metastasis axis that strongly depends on the cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the precise cellular function of TCF7L1 in cancer. However, prior reports suggested that it may have either oncogenic or tumor suppressor properties depending on the cellular context [24][25][26][27][28] . To explore its potential role in EwS, we first analyzed the TCF7L1 expression pattern across 18 cancer entities using publicly available microarray data from the Cancer Cell Line Encyclopedia (CCLE) 29 and from an own study that compiled well-curated microarray data from the same cancer entities 30 .…”
Section: Tcf7l1 Re-expression Inhibits Tumorigenesis In Vitro and In mentioning
confidence: 99%
“…A recent study provided evidence for a tumor-promoting role of TCF7L1 in skin. Overexpression of TCF7L1 increased tumor incidence, promoted tumor growth, and enhanced migration independent of β-catenin [158]. In addition to TCF7L1, Wnt genes are also commonly dysregulated in diverse tumor cells, including prostate, ovarian, colon, and skin cancers [159,160,161,162].…”
Section: Wnt Signaling In Keratinocyte Carcinomasmentioning
confidence: 99%